Children’s Legal Identity at Stake: Reconstructing Maqasid al-Syari'ah through Marriage Isbat Applications by the Second Generation in Pasuruan - Rifqi, Muhammad Jazil; Nadhifah, Nurul Asiya; Hadi, Mukhammad Nur; Junaidy, Abdul Basith; Solikin, Agus (El-Mashlahah, 2025)
The article explored the issue of legal identity among children born from nikah siri (unregistered marriages) in Pasuruan, Indonesia, who pursue isbat nikah to formally legalize their parents’ undocumented married. Based on earlier research that focused primarily on the marital relationship, the study highlighted a generational shift, wherein children from these married are no longer passive observers but active legal participants seeking access to inheritance, educational entitlements, and official guardianship. Utilizing a socio-legal qualitative methodology, the research employed interviews with petitioners, religious court judges, and representatives from the Office of Religious Affairs. The findings found out that isbat nikah serves not only as a corrective legal process but also as a strategic means to reintroduce excluded families into the formal legal framework of the state. From the theoretical view of maqasid al-syari'ah, the study shows how Islamic legal objectives including the preservation of lineage (hifz al-nasl), the pursuit of justice (‘adl), and the safeguarding of dignity (hifz al-‘ird) are being reshaped through judicial interpretation and community practice. The study enriched current discourse on legal pluralism, reform in Islamic family law, and the emergent role of youth in engaging with religious legal institutions. Although its scope is limited to Pasuruan, the research provides a foundation for comparative investigations into how second-generation actors operate within overlapping legal systems across Muslim-majority societies.